2005
DOI: 10.1253/circj.69.802
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Muscle Vasodilation Using Near-Infrared Spectroscopy in Cardiac Patients

Abstract: ver the past 2 decades, many studies have shown that a number of factors contribute to the exercise intolerance of patients with chronic heart failure (CHF). Factors suggested include skeletal muscle underperfusion caused by central hemodynamic alterations such as diminished cardiac output, as well as left ventricular (LV) 1-3 and right ventricular dysfunction, 4 and abnormalities in peripheral mechanisms such as skeletal muscle vasodilation, 5-7 skeletal muscle histology, 8,9 metabolism, 10-14 and muscle oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…[12][13][14][15] It is assumed that the cause of impaired nutritive flow to skeletal muscle is the attenuated vasodilatation of exercising muscle and the attenuation of sympathetic vasoconstriction of non-exercising muscle. [16][17][18] In the present study, blood flow to the exercising muscle was correlated positively with parameters of exercise tolerance. In contrast, blood flow to the non-exercising muscle was not correlated with parameters of exercise tolerance.…”
Section: Blood Flow Redistributionsupporting
confidence: 58%
“…[12][13][14][15] It is assumed that the cause of impaired nutritive flow to skeletal muscle is the attenuated vasodilatation of exercising muscle and the attenuation of sympathetic vasoconstriction of non-exercising muscle. [16][17][18] In the present study, blood flow to the exercising muscle was correlated positively with parameters of exercise tolerance. In contrast, blood flow to the non-exercising muscle was not correlated with parameters of exercise tolerance.…”
Section: Blood Flow Redistributionsupporting
confidence: 58%
“…Muscle blood volume changes measured by NIRS should be interpreted always with caution in terms of insinuating changes in blood flow. Nevertheless studies confirmed the applicability of this parameter comparing the NIRS signal with invasive methods of blood flow measurement (Watanabe et al 2005). Another limitation of the study could be the non-random order of the two experimental conditions.…”
Section: Discussionmentioning
confidence: 78%
“…This device consists of a reflectance mode fiber optic probe coupled to the multi-wavelength spectrometer capable of emitting and detecting light intensity within a range of 680-800 nm. Thus, the relative changes in Hb muscle and HbO 2 , and also the change in HbT, which is related to Hb muscle and HbO 2 and reflects alterations in muscle blood volume, can be calculated (Watanabe et al 2005).…”
Section: Analytical Methods and Equipmentmentioning
confidence: 99%
“…Endothelium-dependent vasodilatation of the peripheral vasculature is impaired in patients with CHF, 32 as a consequence of defective nitric oxide synthase (eNOS) activity. 33 Evidence is accumulating that regular exercise has beneficial effects on vascular reactivity, and that these salutary changes result from exercise-induced increases in blood flow.…”
Section: Discussionmentioning
confidence: 99%